THE EFFECT THAT TRAUMA HAS ON ABUSIVE SITUATIONS AND RELATIONSHIPS - Sarita Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
In the past quarter of a century, there has been a significant increase in the clinical and empirical attention placed on traumatic incidents. Even though humans have been able to endure traumatic situations for ages, there has been a significant advance in the scientific knowledge of trauma in recent history. The individual impacts of trauma on the main victim, or the person who was there during the traumatic event, are the subject of a significant portion of the research and writing that has been done on trauma and posttraumatic stress (Herman, 1997; van der Kolk, McFarlane, & Weisaeth, 1996). The treatment of posttraumatic stress disorder (PTSD; American Psychiatric Association [APA], 2000) has been the predominant focus in the trauma literature. PTSD is a disorder that, by definition, focuses on the intrapersonal effects of traumatic events on the individual trauma survivor.